Akibat Hukum Wanprestasi Atas Perjanjian Lisan Pinjam-Meminjam Oleh Pasangan Kekasih Yang Tidak Terikat Perkawinan - Panjaitan, Wijaya Natalia (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2024)
Introduction: Verbal agreements to borrow stuff and/or money are often made by couples who are not bound by marriage in their daily relationship activities. The impact of this verbal agreement often causes legal problems, which is the breach of contract by one of the parties when the relationship between the couple does not continue to the level of marriage, causing material and immaterial losses to the other party. Purposes of the Research: The purpose of this research is to find out the legal consequences of a breach of the verbal agreement of lending and borrowing by a spouse who is not bound by marriage. Methods of the Research: The research method used is normative juridical research with the type of library research. Results Originality of the Research: The legal consequences of a breach of the verbal lending and borrowing agreement are material and immaterial losses so that a claim for compensation can be filed by filing a lawsuit for breach of contract with the Civil Court.